Real‐time implementation for vulnerability of power components under switching attack based on sliding mode - Seema Yadav; Nand Kishor; Shubhi Purwar; Saikat Chakrabarti; Petra Raussi; Avinash Kumar (IET Cyber-Physical Systems)
Abstract In recent years, cyber security‐related studies in the power grid have drawn wide attention, with much focus on its detection, mainly for data injection type of attacks. The vulnerability of power components as a result of attack and their impact on generator dynamics have been largely ignored so far. With the aim of addressing some of these issues, the authors propose a novel approach using real‐time sliding surface‐based switching attack (SA) construction. This approach targets the circuit breaker, excitation system, and governor system of the generator. The vulnerability of these power components to cyber‐physical attacks and assessment of their potential impact on the stability of generator are discussed. The study is presented to show the progression of cascading generator dynamics on account of single or multiple time instants of SA launched on these power components. The results are discussed according to criteria in terms of deviations in rotor speed of the generator and identify some of possible combinations of power components that are most critical to grid stability. The proposed study is implemented on standard IEEE 3‐machine, 9‐bus network in real‐time digital simulator via transmission control protocol/internet protocol (TCP/IP) communication network established as cyber‐physical system. The sliding surface‐based SA algorithm developed in MATLAB is launched from another computer.